Peer-mentoring in the health education: what are its applications, limitations and strategies for success? (Research, Society and Development, 2021)
This study aimed to investigate the contribution of Peer-Mentoring in basic academic training and continuing education of health professionals, as well as to identify the main limitations, challenges and alternatives to achieve the success of its implementation. This is an integrative review study with systematic search, performed in PubMed, Scopus, Web Of Science, Education Resources Information Center (ERIC) and Virtual Health Library (VHL) databases. Electronic articles, available in full, in Portuguese, English and/or Spanish and published in the last 5 years, were included. Studies of the literature review type, abstracts, letter to the editor, duplicate manuscripts and studies that were not related to the theme were excluded. The following descriptors were combined with the Boolean operators AND and OR: “Peer-Mentoring”, “Peer Group”, “Mentoring”, “Mentors”, “Health Education” and “Education, Medical”. Thirty-one eligible articles were collected, which underwent a full-text analysis and data fiching. The studies were grouped into five categories of analysis: (1) contribution of Peer-Mentoring in the academic training process; (2) impact of Peer-Mentoring on the continuing education of health professionals continuing education; (3) limitations are encountered during the execution of Peer-Mentoring; (4) pedagogical challenges that must be overcome, in the course of Peer-Mentoring; (5) How to achieve success during the implementation and execution of Peer-Mentoring programs? Peer-Mentoring proved to be able to significantly improve the health teaching process. Future perspectives point to a greater adherence by educational institutions to insert peer-mentoring in the pedagogical programs.